Análise de um esquema linear para estimativa de anisotropia local a partir de dados de onda P em experimentos de VSP multiazimutal - MACAMBIRA, Raiza de Nazaré Assunção (Universidade Federal do Pará, 2014)
This study presents an analysis of the linear inversion scheme for estimating anisotropy in the neighborhood of a receiver placed in a well using the vertical components of the slowness and polarization vectors of P-waves measured in multi-azimuth walkaway vertical seismic profile (VSP) surveys. Independently of the medium above the geophone (homogeneous or heterogeneous) and the shape of the well (directional or curved, vertical or sloped), an inversion is performed from a first-order approximation around a reference isotropic medium. The analysis of the inversion scheme considers factors such as the noise level of the data, the type of P-wave, the degree of the anisotropy of the medium, the choice of parameters in the reference isotropic medium and the degree of heterogeneity of the medium.